2010
DOI: 10.1021/nl904207n
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Nanowire Species Synthesized on a Single Chip by Selectively Addressable Horizontal Nanochannels

Abstract: The synthesis of horizontal porous anodic alumina (PAA) structures with individually addressable channel systems is demonstrated. This was achieved by developing a multicontact design of aluminum finger structures (two to five contacts) on silicon wafers. These aluminum contacts were electrically isolated from each other, allowing the individual anodization of each contact at different conditions. This way it is possible to synthesize different pore diameters, pore densities, and channel lengths on a single ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 33 publications
1
28
0
Order By: Relevance
“…They give easy access to self-organized pores with high aspect ratios and tunable pore sizes (Gao et al 2002;Masuda & Fukuda et al, 1995;Krishnan & Thompson, 2007;Nielsch et al, 2000). These pores are then used as a molding system for the synthesis of the desired nanostructures (Xiang et al, 2010). The VLS growth of SiNWs inside the pores of an unsupported PAA template using SiH 4 as the precursor gas has been completed (Bogart et al, 2005;Lew & Redwing, 2003;, as shown in Figure 1.12.…”
Section: Spatial Controlling Via Vls Mechanismmentioning
confidence: 99%
“…They give easy access to self-organized pores with high aspect ratios and tunable pore sizes (Gao et al 2002;Masuda & Fukuda et al, 1995;Krishnan & Thompson, 2007;Nielsch et al, 2000). These pores are then used as a molding system for the synthesis of the desired nanostructures (Xiang et al, 2010). The VLS growth of SiNWs inside the pores of an unsupported PAA template using SiH 4 as the precursor gas has been completed (Bogart et al, 2005;Lew & Redwing, 2003;, as shown in Figure 1.12.…”
Section: Spatial Controlling Via Vls Mechanismmentioning
confidence: 99%
“…Recently, other groups have realised similar horizontally-oriented nanochannels following this idea. [16][17][18][19] In these reports, an aluminium film deposited onto an oxidised silicon substrate was etched in parallel strips and then capped with a silicon oxide layer. [16][17][18][19] The short edges of the strips were dipped into the electrolyte and the anodisation proceeded along their lengths.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19] In these reports, an aluminium film deposited onto an oxidised silicon substrate was etched in parallel strips and then capped with a silicon oxide layer. [16][17][18][19] The short edges of the strips were dipped into the electrolyte and the anodisation proceeded along their lengths. Cojocaru and coworkers [17] have shown scanning electron microscopy (SEM) and transmission electron microscopy (TEM) images of horizontal pores, 200-300 nm long, with pore diameters between 3-4 nm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, such structure, usually called Porous Anodic Alumina (PAA) membrane, has been widely used in the field of nanowires/nanotubes growth because of its easilycontrollable features, and the high aspect ratio of the pores [7,8,9,10,11]. Despite this progress, SiNWs growth still lacks a good control and understanding of the mechanisms that rule their formation [5,12,13,14], especially in such a very particular case where a confined growth occurs.…”
Section: Introductionmentioning
confidence: 99%